Analysis of differences in physical fitness levels of extracurricular futsal students: Survey studies on urban and rural environments - Rubiyatno; Rahmat Putra Perdana; Ilham Surya Fallo; Zainal Arifin; Ardi Nusri; Didi Suryadi; Mikkey Anggara Suganda; Ella Fauziah (IP Iermakov S.S., 2023)
Background and Study Aim. Maintaining physical fitness is essential to perform daily tasks with the required level of efficiency. By being physically fit to design an ideal training plan. This study aims to determine the profile and differences in the level of physical fitness in futsal extracurricular students in urban and rural environments. Materials and Methods. The method in this study used a quantitative approach through surveys with researchers providing a physical test and measurement (TKJI) for 13-15 year old to futsal extracurricular students. This research was conducted at SMP Negeri 11 Pontianak City and SMP Negeri 3 Sukadana, Kayong Utara Regency. Purposive sampling technique in determining the sample so that 40 students were sampled. To see the difference through the normality prerequisite test stage, homogeneity test and t test. Data analysis was assisted by using the SPSS Version 26 application. Results. According to the study findings, the average physical fitness score of futsal extracurriculars in urban areas was 12.50, while the average in rural environments was 15.15. Furthermore, a significant difference between urban and rural extracurricular futsal contexts is shown by a significance value of 0.000 < 0.05. Conclusions. This finding supports the hypothesis that the level of physical fitness necessary for extracurricular futsal varies significantly between urban and rural areas. This study provides evidence that futsal extracurricular students in rural areas have better physical fitness than students in urban areas. These findings can be a reference for sports practitioners to be able to develop exercise programs to improve the physical fitness of children aged 13-15 years, especially for playing futsal.